Verbal Reports of Proficient Readers In Coping With Unfamiliar Words - Kusumarasdyati Kusumarasdyati (Universitas Negeri Malang, 2016)
The present study reports the actual strategy use of good readers when they face hindrance in the form of unfamiliar words. Eight undergraduates majoring in English at Surabaya State University performed think-aloud while reading two texts to find out how they coped with such difficulties. The verbal protocol indicated that half of the participants mainly relied on a bilingual (English-Indonesian) dictionary to attack unfamiliar words, and only one of them preferred to use a monolingual (English-English) one. Two of them employed context cues to infer the meaning of the words, while one participant combined the use of context cues and a monolingual dictionary as the major strategy. All but one of the participants skipped some of lexical items whose meaning was unknown to them, especially when these words did not have a key contribution to the meaning of the whole text.